Postoperative follow up Challenge in Paediatric Cataract Surgery in Nepal - Shrestha, UD (Journal of Nepal Paediatric Society, 2011)
Introduction: Paediatric ophthalmology is a branch of specialty care for the health of the eyes of children. It focuses on the removal of paediatric cataracts and management of refractive error, strabismus etc. Perioperative and post-operative challenges related to paediatric cataract are known to all ophthalmologists worldwide. However, in a developing country like Nepal the main challenge of these patients are the post-operative follow up. The aim of the study is to find out the ways to reduce the post-operative follow up challenges in paediatric cataract surgery. Hence the ophthalmic assistants in the community eye centers need to be trained to examine the eyes of children. Materials and Methods: This was a retrospective study. A review of patient records, operated from July 2006 to December 2007, at Tilganga Institute of Ophthalmology was done. One hundred eyes of 69 patients were operated during the study period. Results: Follow-up assessment of visual acuity was available for 19 eyes only at the end of six weeks. Conclusion: At the end of six postoperative weeks, refractive status is important. This helps to prescribe the glasses to children as per need. If the post-operative visual status is not known, it is as equal as not performing the surgery. Ophthalmic assistants at community eye centers need to be trained to evaluate and record postoperative visual status of the paediatric age group. For this regular training and refreshers course on the pediatric eye care service is being conducted at the tertiary level for the ophthalmic assistants. This is more practical in the developing countries like Nepal. Key words: Cataract; Intraocular lens; Pediatric cataract surgery DOI: http://dx.doi.org/10.3126/jnps.v31i3.4062 J Nep Paedtr Soc 2011;31(3):198-201